EFFECTIVENESS OF PRIMARY INTRAOSSEOUS ANESTHESIA IN THE ENDODONTIC TREATMENT OF MANDIBULAR MOLARS WITH IRREVERSIBLE PULPITIS - Emiliya Simeonova; Snezhana Tsanova; Plamen Zagorchev (Peytchinski Publishing, 2020)
Objective: The aim of the study was to investigate the effectiveness of primary intraosseous anesthesia (IO) in the endodontic treatment of lower molars with irreversible pulpitis. Material and method: The subject of the study was 30 clinically healthy patients diagnosed with irreversible pulpitis of mandibular first or second molars. All of endodontic treatments were performed in a single visit. IO was performed with computer assisted system Quicksleeper. Our goal was to investigate the presence of pain during various parts of endodontic treatment with Visual Analog Scale. The pain level was registered at the end of the following parts of the endodontic treatment: 1-st part - after preparation of the endodontic access; 2-nd part - after determining the working length for all root canals; 3-rd part - after root canal preparation. Results: No pain was registered either in preparation of endodontic access or in determining the working length for all root canals. Only four patients (14.3%) registered mild pain during root canal preparation, which did not interfere of the endodontic treatment. In the 3-rd part of endodontic treatment it was registered moderate and severe pain respectively from 3.5% and 7.2% of patients, requiring a supplemental anesthesia. Conclusion: The IO can be use as primary method of analgesia that provides reliable pulpal anesthesia for routine endodontic treatment.